TWICE TOMAS DIANISKA. Above two texts by the winner of the the Best Czech Play of 2019 and 2020 - bergmannova, Pavla (Bohemica Olomucensia, 2023)
The study focuses on two plays of the winner of the Best Czech Play of 2019 and 2020 - talented author Tomas Dianiska. Title Trans, Points, Seconds was inspired by the scandalous fate of a Czech athlete Zdena Koubkova, who was in fact a man, The Magnificent 294 is a documentary fiction based on a real event - the assassination of Reichsprotektor Heydrich. Dianiska perceives historical themes with controversial optics. His texts are full of black humour and irony, as well as frequent use of pop culture references.
Keywords: Tomas Dianiska; Trans; Points; Seconds; The Magnificent 294; drama; history; irony; black humor; absurdity